Improving Inconsistency Resolution with Side-effect Evaluation and Costs - Küster, Jochen; Ryndina, Ksenia; Gall, Harald (Proceedings of the ACM/IEEE 10th International Conference on Model Driven Engineering Languages and Systems (MODELS 2007), Nashville, TN (USA))

Generation of Business Process Models for Object Life Cycle Compliance - Ryndina, Ksenia; Küster, Jochen; Gall, Harald (Proceedings of the BPM Demonstration Program (satellite event of the 5th International Conference on Business Process Management (BPM 2007)), Brisbane (Australia))

Smart Teams: Simulating Large Robotic Swarms in Vast Environments - Arens, Stephan; Buss, Alexander; Deck, Helena; Dynia, Miroslaw; Fischer, Matthias; Hagedorn, Holger; Isaak, Peter; Kutylowski, Jaroslaw; Meyer auf der Heide, Friedhelm; Nesterow, Viktor; Ogiermann, Adrian; Stobbe, Boris; et al. (Proceedings of the 4th International Symposium on Autonomous Minirobots for Research and Edutainment)
We consider the problem of exploring an unknown environment using a swarm of autonomous robots with collective behavior emerging from their local rules. Each robot has only a very restricted view on the environment which makes cooperation difficult. We introduce a software system which is capable of simulating a large number of such robots (e.g. 1000) on highly complex terrains with millions of obstacles. Its main purpose is to easily integrate and evaluate any kind of algorithm for controlling the robot behavior. The simulation may be observed in real-time via a visualization that displays both the individual and the collective progress of the robots. We present the system design, its main features and underlying concepts.

Reusable Architectural Decision Models for Enterprise Application Development - Zimmermann, Olaf; Gschwind, Thomas; Küster, Jochen; Leymann, Frank; Schuster, Nelly (Proceedings the conference on Quality of Software-Architectures (QoSA 2007), Medford, MA (USA))

"Modelchecking" - Eine Methode zur Verbesserung der Softwarequalität - Gehrke, Matthias; Güldali, Baris; Kindler, Ekkart

Investigation of multicast-based mobility support in all-IP cellular networks - Festag, Andreas; Karl, Holger; Wolisz, Adam (Wireless Communications and Mobile Computing)

WASP - Wirelessly Accessible Sensor Populations: A Project Overview - van der Stok, Peter; Karl, Holger; De Ambroggi, Fabio; Decotignie, JeanDominique; Siegemund, Frank; Lokhorst, Kees; Hellenschmidt, Michael (Constructing Ambient Intelligence - AmI 2007 Workshops Darmstadt, Germany, November 7-10, 2007 Revised Papers)

Outage probability analysis of cooperative transmission protocols without and with network coding: inter-user channels based comparison - H. Woldegebreal, Dereje; Valentin, Stefan; Karl, Holger (Proceedings of the 10th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2007, Chania, Crete Island, Greece, October 22-26, 2007)

Traffic-Aware Asymmetric Cooperation Diversity for Media Streaming in Wireless Networks - Valentin, Stefan; von Malm, Holger; Karl, Holger (Proceedings of the IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2007, 3-7 September 2007, Athens, Greece)

Integrating multiuser dynamic OFDMA into IEEE 802.11a and prototyping it on a real-time software-defined radio testbed - S. Lichte, Hermann; Valentin, Stefan; Eitzen, Falk; Stege, Matthias; Unger, Carsten; Karl, Holger (3rd International ICST Conference on Testbeds and Research Infrastructures for the Development of Networks and Communities, TridentCom 2007, Orlando, Florida, USA, May 21-23 2007)

Finanzwirtschaftliche Analyse der schenkungsteuerlichen Zehnjahresregel - Kundisch, Dennis; Pfeiler, F.; Schiefele, V. (Steuer und Wirtschaft)

MuPAD: eine Einführung - Rapin, Gerd; Wassong, Thomas; Wiedmann, Stefan; Koospal, Stefan
Keywords: mupad

Graphentheoretische Konzepte in der Gymnasialen Oberstufe: Ein Unterrichtsentwurf unter Berücksichtigung der Neuen Medien - Wassong, Thomas

Customer Portfolio Management in E-Commerce – A Risk Management Perspective - Kundisch, Dennis; Sackmann, S.; Ruch, M. (INFORMS International Puerto Rico 2007 Meeting)

Außerbörslicher Emittentenhandel: Handelsplatzwahl von Online-Investoren - Kundisch, Dennis; Stuber, T. (Wirtschaftsinformatik 2007 - eOrganisation: Service-, Prozess-, Market-Engineering)

Bank controlling using Basel II-data: Are internal approaches dispensable? - Kundisch, Dennis; Loehner, F.; Rudolph, D.; Steudner, M.; Weiss, C. (2007 Enterprise Risk Management Symposium Monograph)

Spezifizierung des Kano-Modells zur Messung von Kundenzufriedenheit - Buhl, H. U.; Kundisch, Dennis; Schackmann, N.; Renz, A. (Wirtschaftsinformatik 2007 - eOrganisation: Service-, Prozess-, Market-Engineering)

Feedbackgespräche: Überstrapaziert, missverstanden und bedeutungslos? Ganz im Gegenteil: Best Practise bei der Deutschen Bahn - Terlinde, P; Giardini, A; Kabst, Rüdiger; Halbach, J; Pelchrzim, H

Strategische Personalentwicklung: Wenn dem Bildungscontroller die Ziele fehlen - Giardini, A; Kabst, Rüdiger

Funktionale Äquivalente zur Personalplanung : Eine empirische Studie zur Personalplanung klein- und mittelständischer Unternehmen auf Basis des Cranet - Matiaske, W; Holtmann, D; Kabst, Rüdiger (Planung in kleinen und mittleren Unternehmen, Jahrbuch der KMU-Forschung und -Praxis 2007)

Leistungsbeurteilung und -vergütung in der privaten Wirtschaft und im öffentlichen Dienst: Eine vergleichende Betrachtung auf Basis des „Cranfield-Projects“ 1995-2005 - Giardini, A; Kabst, Rüdiger (Leistungsvergütung im Öffentlichen Dienst)

Preventing E-mail Spam: The Conceptualization and the Analysis of an Infrastructure Framework - Schryen, Guido
Spamming remains a form of Internet abuse, which burdens the Internet infrastructure, is generally regarded as an annoyance, and is said to cause a huge economic harm. Many technological, organizational, and legislative anti-spam measures have already been proposed and implemented, but have not led to any substantial decrease in the number of spam e-mails. We propose a scalable and flexible infrastructure framework that integrates several anti-spam measures and that features both a technological and an organizational facet. The key element of our infrastructure is a new organizational unit that reliably and transparently limits the number of e-mails that can be sent per day and per account. We also analyze the proposed framework in terms of its theoretical effectiveness, the required resources, and its limitations.
Keywords: Email; Infrastructure; Internet; Spam

Joint Venture Performance: A Meta-Analysis - Isidor, R; Hornung, F; Kabst, Rüdiger

Pre-and post entry learning of young technology firms: antecedents of objective and tacit knowledge and performance implications - Schwens, C; Kabst, Rüdiger

Self-Organization in Sensor and Actor Networks - Dressler, Falko
Self-organization is a rather fascinating concept that enables systems consisting of huge numbers of autonomously acting subsystems to perform a collective task. Moreover, self- organizing systems show an overall behavior that cannot easily be predicted or even preprogrammed in a scalable way. It was in the early 1960ies that people like Ashby and Eigen investigated self-organization properties in (natural) systems. Since these days, a great number of (technical) solutions have been developed, which, either on purpose or unintentionally, inherently the basic concepts of self-organization. The aim of this book is to investigate the concepts of self-organization in the context of autonomous sensor and actor networks. The primary objective is to categorize the basic self-organization methods and to survey techniques for communication and coordination in massively distributed systems according to the developed classification scheme. Basically, two possible approaches can be thought of for organizing this book. First, we could start analyzing sensor and actor network technology and figure out what basic mechanisms are employed and how these relate to self-organization. A second approach would be to introduce self-organization as a methodology, apparently used everywhere in our life (in nature and in technical systems), and afterwards to continue with technical issues in sensor and actor networks searching for previously learned self-organization methods. I decided to follow the second approach in order to keep the focus on self-organization while studying the term in the world of sensor and actor networks. The term self-organization is still often misunderstood and misinterpreted. Therefore, this textbook is intended to be a basis for a better understanding of the concepts of self-organization, especially in the domain of sensor and actor networks. It provides a stepwise introduction of definitions, methodologies, and corresponding techniques relevant in the context of self-organization. Recent advances in miniaturization and wireless communication enabled the development of low-cost sensor nodes. Additionally, new application domains of sensor and actor networks emerged that demand for huge numbers of interacting devices. Thus, the relevance of self-organization methods is rapidly increasing as it is considered the primary control paradigm for distributed and massively distributed systems. The reader will see that self-organization has a number of advantages compared to other control paradigms. So, it becomes possible to operate huge numbers of collaborating subsystems even in case of limited resources, unreliable communication, and in case of massive failures of single systems. Unfortunately, these advantages are accompanied by some rather annoying side effects such as the increasing complexity and a nondeterministic behavior. By using optimal combinations of the basic methods of self-organization, these disadvantages can be minimized to some extent. According to the objective of this textbook - to study sensor and actor networks - the most relevant domains of communication and coordination are deeply investigated based on well-known algorithms and mechanisms and a number of case studies. This includes networking aspects of medium access control, ad hoc routing, data-centric communication, and clustering techniques. Additionally, control mechanisms for cooperation, task and resource allocation, and collaborative actuation are investigated. The book is concluded by a brief introduction of the domain of bio-inspired algorithms. This study is included for two reasons. First, to demystify the term bio-inspired networking, and secondly, to show the capabilities of such bio-inspired approaches.

Einsatz von E-Portfolios zur Förderung von studentischen Lerngemeinschaften im Hochschulstudium. - Sporer, Thomas; Jenert, Tobias; Strehl, Bernhard; Noack, Patrick Ole (DeLFI Workshops)
Keywords: E-Portfolios; Lerngemeinschaften; Praxisgemeinschaften; Projektgruppen; Hochschulstudium; informelles Lernen

Learning about innovation and knowledge creation in higher education. - Sporer, Thomas; Jenert, Tobias; Reinmann, Gabi (4. Konferenz Professionelles Wissensmanagement - Erfahrungen und Visionen)

Semivirtuelle Lernumgebung zum wissenschaftlichen Arbeiten als Ergänzung des Studienangebots der Universität Augsburg - Heinze, Nina; Sporer, Thomas; Jenert, Tobias (Deutsche Gesellschaft für Informationswissenschaft und Informationspraxis: Tagungen der Deutschen Gesellschaft für Informationswissenschaft und Informationspraxis)
Keywords: Wissenschaftliches Arbeiten; Blended Learning; Tutoring

Student Learning Communities in the Project-Centered Study Program" Problem-Solving Competencies" - Sporer, Thomas; Heinze, Nina; Jenert, Tobias; Reinmann, Gabi
Keywords: Problem Solving Competencies; E-Portfolio

Begleitstudium Problemlösekompetenz (Version 2.0). Infrastruktur für studentische Projekte an Hochschulen - Sporer, Thomas; Reinmann, Gabi; Jenert, Tobias; Hofhues, Sandra (Studieren neu erfinden - Hochschule neu denken)

Fallstudie: Social Software im Hochschulstudium - Sporer, Thomas; Jenert, Tobias (Enterprise 2.0 - Planung, Einführung und erfolgreicher Einsatz von Social Software im Unternehmen)

p-Shell Rabi-flopping and single photon emission in an InGaAs/GaAs quantum dot - Ester, P.; Lackmann, L.; Hübner, M.C.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Bichler, M. (Physica E: Low-dimensional Systems and Nanostructures)
Very clean single photon emission from a single InGaAs/GaAs quantum dot is demonstrated by the use of a coherent optical state preparation. We present a concept for single photon emission, which uses p-shell Rabi-flopping followed by a sequence of relaxation and recombination. The proof of the (clean) single photon emission is performed by photon correlation measurements.
Keywords: Antibunching; Single photon emission; Rabi oscillation; Coherent manipulation

On the asymptotic variance in nonparametric regression with fractional time-series errors - Feng, Yuanhua (Journal of Nonparametric Statistics)

Modelling financial time series with SEMIFAR GARCH model - Feng, Yuanhua; Beran, J.; Yu, K. (IMA Journal of Management Mathematics)

Semiparametric Modeling of Stochastic and Deterministic Trends and Fractional Stationarity - Beran, Jan; Feng, Yuanhua; Franke, Günter; Hess, Dieter; Ocker, Dirk (Processes with Long-Range Correlations)

Local Polynomial Estimation with a FARIMA-GARCH Error Process - Beran, Jan; Feng, Yuanhua (Bernoulli)

Special Issue: Quantile Regression

Kundenbindung durch Weiterempfehlung? Eine experimentelle Untersuchung der Wirkung positiver Kundenempfehlungen auf die Bindung des Empfehlenden. - Eggert, Andreas; Helm, Sabrina; Garnefeld, Ina (Marketing ZfP)

Immigration policy and the labor market: the German experience and lessons for Europe - Zimmermann, Klaus F; Bonin, Holger; Fahr, Rene; Hinte, Holger

On the inverse relationship between unemployment and absenteeism: evidence from natural experiments and worker heterogeneity - Fahr, Rene; Frick, Bernd

Incentives to invest in the human capital of temporary agency workers - Schmidt, Stephanie; Thommes, Kirsten (German Journal of Human Resource Management)

Outsourcing HR functions. Development of an explanatory approach to firms'(non-existent) demand for personnel services - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (Management Revue)

Kooperation und Konkurrenz in Personaldienstleistungsbeziehungen - Bähring, Katrin; Thommes, Kirsten (Kooperation und Konkurrenz)

Paderborner Forschungs- und Entwicklungswerkstatt - Forschungsfragen und -konzepte der beruflichen Bildung

Lernen in medienbasierten kooperativen Lernumgebungen - Modellversuch KooL

Qualifizierung von Berufs- und Wirtschaftspädagogen zwischen Professionalisierung und Polyvalenz - Kremer, H.-Hugo; Tramm, T. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Mentoring-Modell Paderborn - Konzept und erste Erfahrungen - Burda, A.; Kremer, H.-Hugo; Pferdt, F. G. (Zeitschrift für Hochschulentwicklung)

Selbstgesteuertes Lernen in medienbasierten kooperativen Lernumgebungen - Kremer, H.-Hugo (Lernen in medienbasierten kooperativen Lernumgebungen - Modellversuch KooL)

Kooperative Lernaufgaben als Instrumente der Curriculumentwicklung - Kremer, H.-Hugo (Lernen in medienbasierten kooperativen Lernumgebungen - Modellversuch KooL)

Structural and Behavioural Compatibility of Graphical Service Specifications - Heckel, Reiko; Cherchago, Alexey (Logic and Algebraic Programming)

Software-Qualität - überall! - Excel-lente Software - Bals, Jan-Christopher; Christ, Fabian; Engels, Gregor; Sauer, Stefan (Forschungsforum Paderborn)

A Model-Driven Approach to Discovery, Testing and Monitoring of Web Services - Lohmann, Marc; Mariani, Leonardo; Heckel, Reiko (Test and Analysis of Web Services)
Service-oriented computing is distinguished by its use of dynamic discovery and binding for the integration of services at runtime. This poses a challenge for testing, in particular, of the interaction between services. We propose a model-driven solution to address this challenge. Service descriptions are promoted from largely syntactical to behavioural specifications of services in terms of contracts (pre-conditions and effects of operations), expressed in a visual UML-like notion. Through mappings to semantic web languages and the Java Modeling Language (JML) contracts support the automatic discovery of services as well as the derivation of test cases and their execution and monitoring. We discuss an extended life cycle model for services based on the model-driven approach and illustrate its application using a model of a hotel reservation service.

Architectural Style-based Modeling and Simulation of Middleware for Mobile Systems - Guo, Ping
Today, mobility is one of the most important market and technology trend within information and communication technology. As the demand for rapid deployment of dependable mobile applications increases, middleware for mobile systems is emerging as one of the most active areas of system research in mobility. The middleware is a set of distributed software services that exists between distributed operating systems and mobile applications. The key to the middleware is to provide support across the mobile application domains, help application developers overcome the complexity and problems brought by mobility, and enhance dependability and usability of developed mobile applications. The criticality and pervasiveness of middleware for mobile systems is continually growing. However, the design and development of the middleware are difficult tasks, and it is not easy to ensure the quality of a developed middleware. This is mainly caused by the increasing complexity of the middleware. In addition, the great diversity of this area makes it very difficult for the designers to reuse the already established design knowledge or successful experience when building new systems. All these make the design process quite inefficient and unpredictable, and therefore risking the project. “One man’s magic is another man’s engineering”. Engineering design is much more routine than innovative. Founding on this fundamental notion in software engineering, we develop an architectural style-based approach to deal with the problems in the thesis. We build architectural styles for a class of related middleware. The style represents a common form of design, which originates from the results that practitioners have achieved in one area. The style is formulated to repeat successes and avoid failures from previous projects. When building a new middleware, the designers and developers do not need to explore all possible alternatives for its supported architecture. Instead, they can use the architectural style that is effective for the middleware. They can define the design as instances of the style, or they can use the style as a reference model for further improvement and development. By structuring the design space for a family of related middleware, the style can drastically simplify the process of building a middleware, reduce costs of implementation through reusable infrastructure, and improve system integrity through style-specific analysis and checks. We develop the approach based on UML-like meta modeling and graph transformation techniques to support sound methodological principles, powerful modeling, formal analysis and refinement. The approach consists of several main parts: the modeling language that supports specification of the style and mobility, the refinement formalization that ensures that an abstract style is correctly refined to a concrete one, as well as the consistency check framework that validates behavioral consistency between two styles on different abstract layers. With the Fujaba simulation tool support, we also develop a style-based engineering process that helps us to efficiently develop correct and consistent styles. Besides, it allows a seamless integration of our approach into the well-known object oriented design. By providing a concrete example of how to construct the style for a class of related middleware, and how to use the style to help the design and development of a new middleware, we show that the architectural style-based approach is useful and practical.

Constructing an Emblematic Northern Space. The New Brighton Photographs of Martin Parr and Tom Wood - Tönnies, Merle (Spatial Practices 2)

Quantum dots as tunable scatterers for 2D- and 1D-electron systems - Marquardt, Bastian; Russ, Marco; Lorke, Axel; Meier, Cedrik; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

Silicon nanoparticles: Absorption, emission, and the nature of the electronic bandgap - Meier, Cedrik; Gondorf, Andreas; Lüttjohann, Stephan; Lorke, Axel; Wiggers, Hartmut (Journal of Applied Physics)

Technique for tilting GaAs photonic crystal nanocavities out of plane - Meier, Cedrik; Hennessy, Kevin (Applied Physics Letters)

Temperature-induced crossover between bright and dark exciton emission in silicon nanoparticles - Lüttjohann, S; Meier, Cedrik; Offer, M; Lorke, A; Wiggers, H (Europhysics Letters (EPL))

Effect of User Mobility in Coded Cooperative Systems with Joint Partner and Cooperation Level Selection - Valentin, Stefan; Karl, Holger (IEEE Wireless Communications and Networking Conference, WCNC 2007, Hong Kong, China, 11-15 March, 2007)

Multi-rate Relaying for Performance Improvement in IEEE 802.11 WLANs - Marie Feeney, Laura; Cetin, Bilge; Hollos, Daniel; Kubisch, Martin; Mengesha, Seble; Karl, Holger (Wired/Wireless Internet Communications, 5th International Conference, WWIC 2007, Coimbra, Portugal, May 23-25, 2007, Proceedings)

Analysis of Model Transformations via Alloy - Anastasakis, Kyriakos; Bordbar, Behzad; Küster, Jochen (Proceedings of the workshop on Model-Driven Engineering, Verification and Validation (MoDeVVA 2007), Nashville, TN (USA))

Towards Model-Driven Unit Testing - Engels, Gregor; Güldali, Baris; Lohmann, Marc (Proceedings of the 2006 International Conference on Models in Software Engineering (MoDELS 2006))
The Model-Driven Architecture (MDA) approach for constructing software systems advocates a stepwise refinement and transformation process starting from high-level models to concrete program code. In contrast to numerous research efforts that try to generate executable function code from models, we propose a novel approach termed model-driven monitoring. On the model level the behavior of an operation is specified with a pair of UML composite structure diagrams (visual contract), a visual notation for pre- and post-conditions. The specified behavior is implemented by a programmer manually. An automatic translation from our visual contracts to JML assertions allows for monitoring the hand-coded programs during their execution. In this paper we present an approach to extend our model-driven monitoring approach to allow for model-driven unit testing. In this approach we utilize the generated JML assertions as test oracles. Further, we present an idea how to generate sufficient test cases from our visual contracts with the help of model-checking techniques.

Analysis of UML Activities with Dynamic Meta Modeling Techniques - Soltenborn, Christian; Engels, Gregor (Symposium "A Formal Semantics for UML" (satellite event of the MoDELS conference 2006), Genova (Italy))

Consistency of Business Process Models and Object Life Cycles - Ryndina, Ksenia; Küster, Jochen; Gall, Harald (Models in Software Engineering (1st Workshop on Quality in Modeling at MoDELS 2006, Genoa (Italy)))

On the Pitfalls of UML Activity Modeling - Schattkowsky, Tim; Förster, Alexander (Proceedings of the ICSE workshop on Modeling in Software Engineering (MISE 2007), Minneapolis, MN (USA))
With the introduction of new Petri net-like semantics for Activities in UML 2.0, these have become a complete language for modeling behavior. Thus, UML Activities are nowadays investigated for application in many areas from embedded systems to business process modeling. However, some issues have been discovered that currently seem to limit the practical applicability of Activities. In this paper, we present an overview of the identified semantic and syntactic problems, and point at possible solutions and directions for future research.

Strong spin–orbit interactions in carbon doped p-type GaAs heterostructures - Grbić, B.; Leturcq, R.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Aharonov–Bohm oscillations in p-type GaAs quantum rings - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

High sensitivity far-infrared detection by resonant inter-Landau-level scattering - Notthoff, C.; Lorke, A.; Reuter, Dirk (Physica E: Low-dimensional Systems and Nanostructures)

Aharonov–Bohm effect of quantum Hall edge channels - Giesbers, A.J.M.; Zeitler, U.; Reuter, Dirk; Wieck, A.D.; Biasiol, G.; Sorba, L.; Maan, J.C. (Physica E: Low-dimensional Systems and Nanostructures)

Magnetic-field-induced modification of the wave-functions in InAs quantum dots - Lei, W.; Wibbelhoff, O.; Notthoff, C.; Marquardt, B.; Reuter, Dirk; Wieck, A.D.; Lorke, A. (Physica E: Low-dimensional Systems and Nanostructures)

Influence of In0.15Ga0.85As capping layers on the electron and hole energy levels of InAs quantum dots - Richter, Mirja; Reuter, Dirk; Duboz, Jean-Yves; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

Capacitance–voltage spectroscopy of post-growth annealed InAs quantum dots - Reuter, Dirk; Roescu, Razvan; Mehta, Minisha; Richter, Mirja; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Site-selective growth of self-assembled InAs quantum dots on focused ion beam patterned GaAs - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A.D.; Remhof, A. (Physica E: Low-dimensional Systems and Nanostructures)

Quantum dots as tunable scatterers for 2D- and 1D-electron systems - Marquardt, Bastian; Russ, Marco; Lorke, Axel; Meier, Cedrik; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

A comparison: 2D electron- and hole systems in the fractional quantum Hall regime - Hadzibrahimovic, Adriana; Dethlefsen, Annelene F.; Reuter, Dirk; Wieck, Andreas D.; Tranitz, Hans-Peter; Wegscheider, Werner; Haug, Rolf J. (Physica E: Low-dimensional Systems and Nanostructures)

Hot-electron bend resistance in a ballistic GaAs/AlGaAs cross junction - Wiemann, M.; Cetinkaya, A.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magneto-ballistic effects in non-centrosymmetric GaAs/AlGaAs cross junctions - Wieser, U.; Knop, M.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magneto-optical probing of weak disorder in a two-dimensional hole gas - Bryja, Leszek; Wójs, Arkadiusz; Misiewicz, Jan; Potemski, Marek; Reuter, Dirk; Wieck, Andreas (Physical Review B)

Spin-controlled LEDs and VCSELs - Hövel, S.; Gerhardt, N. C.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W. (physica status solidi (a))

Subsecond Spin Relaxation Times in Quantum Dots at Zero Applied Magnetic Field Due to a Strong Electron-Nuclear Interaction - Oulton, R.; Greilich, A.; Verbin, S. Yu.; Cherbunin, R. V.; Auer, T.; Yakovlev, D. R.; Bayer, M.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Sequential and cotunneling behavior in the temperature-dependent thermopower of few-electron quantum dots - Scheibner, R.; Novik, E. G.; Borzenko, T.; König, M.; Reuter, Dirk; Wieck, A. D.; Buhmann, H.; Molenkamp, L. W. (Physical Review B)

Exciton fine structure inInGaAs∕GaAsquantum dots revisited by pump-probe Faraday rotation - Yugova, I. A.; Greilich, A.; Zhukov, E. A.; Yakovlev, D. R.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Robust manipulation of electron spin coherence in an ensemble of singly charged quantum dots - Greilich, A.; Wiemann, M.; Hernandez, F. G. G.; Yakovlev, D. R.; Yugova, I. A.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Universal behavior of the electrongfactor inGaAs∕AlxGa1−xAsquantum wells - Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Kiselev, A. A.; Bayer, M.; Petrov, V. V.; Dolgikh, Yu. K.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Charge and spin dynamics in a two-dimensional electron gas - Pugžlys, A; Rizo, P J; Ivanin, K; Slachter, A; Reuter, Dirk; Wieck, A D; Wal, C H van der; Loosdrecht, P H M van (Journal of Physics: Condensed Matter)

Magnetic and structural properties of Gd-implanted zinc-blende GaN - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Wieck, A. D.; Ney, V.; Kammermeier, T.; Ney, A.; Schörmann, J.; Potthast, S.; As, D. J.; Lischka, K. (Applied Physics Letters)

Experimental imaging and atomistic modeling of electron and hole quasiparticle wave functions inInAs∕GaAsquantum dots - Bester, G.; Reuter, Dirk; He, Lixin; Zunger, A.; Kailuweit, P.; Wieck, A. D.; Zeitler, U.; Maan, J. C.; Wibbelhoff, O.; Lorke, A. (Physical Review B)

Focused ion beam implantation induced site-selective growth of InAs quantum dots - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A. D.; Remhof, A. (Applied Physics Letters)

Nuclei-Induced Frequency Focusing of Electron Spin Coherence - Greilich, A.; Shabaev, A.; Yakovlev, D. R.; Efros, Al. L.; Yugova, I. A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Science)

Measurement of the specific heat of a fractional quantum Hall system - Schulze-Wischeler, F.; Zeitler, U.; v. Zobeltitz, C.; Hohls, F.; Reuter, Dirk; Wieck, A. D.; Frahm, H.; Haug, R. J. (Physical Review B)

Systematic study of carrier correlations in the electron-hole recombination dynamics of quantum dots - Berstermann, T.; Auer, T.; Kurtze, H.; Schwab, M.; Yakovlev, D. R.; Bayer, M.; Wiersig, J.; Gies, C.; Jahnke, F.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

The Influence of Device Geometry on Many-Body Effects in Quantum Point Contacts: Signatures of the 0.7 Anomaly, Exchange and Kondo - Koop, E. J.; Lerescu, A. I.; Liu, J.; van Wees, B. J.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Journal of Superconductivity and Novel Magnetism)

CYCLOTRON RESONANCE IN COUPLED BILAYERS IN HIGH MAGNETIC FIELDS - GÜRTLER, A.; ZEITLER, U.; MAAN, J. C.; Reuter, Dirk; WIECK, A. D. (International Journal of Modern Physics B)

Aharonov-Bohm Oscillations in the Presence of Strong Spin-Orbit Interactions - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physical Review Letters)

Spin Coherence of Holes inGaAs/(Al,Ga)AsQuantum Wells - Syperek, M.; Yakovlev, D. R.; Greilich, A.; Misiewicz, J.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Evidence for the Luttigger liquid density of states in transport across the incompressible stripe at fractional filling factors - Deviatov, E. V; Kapustin, A. A; Dolgopolov, V. T; Lorke, A; Reuter, Dirk; Wieck, A. D (Europhysics Letters (EPL))

Hole levels in InAs self-assembled quantum dots - Blokland, J. H.; Wijnen, F. J. P.; Christianen, P. C. M.; Zeitler, U.; Maan, J. C.; Kailuweit, P.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Bildungsstandards in der Berufsbildung – Kompetenzen messen auf Basis des Rasch-Modells. Konzeption und Erprobung der Messung - Beutner, Marc (Paderborner Forschungs- und Entwicklungswerkstatt)

Die Förderung interkulturellen Verständnis in der beruflichen Bildung - Beutner, Marc (Fremde Kulturen verstehen – fremde Kulturen lehren. Theorie und Praxis der Vermittlung interkultureller Kompetenz)

Stierstorfer, K. / L. Volkmann (Hg.): Kulturwissenschaft Interdisziplinär - Tönnies, Merle (Anglistik. International Journal of English Studies)